Self‐Assembled Polymeric Materials: Design, Morphology, and Functional‐Oriented Applications. Issue 14 (14th January 2022) - Hu, Shoukui; Yan, Jinhao; Yang, Guangwei; Ma, Chao; Yin, Jun
Abstract: This Review focuses on the current research advances of the synthesis of various amphiphilic block copolymers (ABCs), such as conventional ABCs and newly presented polyprodrug amphiphiles, and the development of corresponding self‐assemblies in selective solvents driven by the intermolecular interactions, like noncovalent hydrophobic interactions, π – π interactions, and hydrogen bonds, between ABCs or preformed small polymeric nanoparticles. The design of these assemblies is systematically introduced, and the diverse examples concerning the unique assembly structures along with the fast development of their exclusive properties and various applications in different fields are discussed. Possible perspectives on the existential challenges and glorious future are elucidated finally. It is hoped that this Review will provide a convenient way for readers to motivate more evolutional innovative concepts and methods to design next generation of novel polymeric nanoassemblies, and fill the gap between material design and practical applications. Abstract : This review focuses on the current research advances of the design, morphology, and functional‐oriented applications of amphiphilic block copolymers (ABCs). Conventional self‐assembly by ABCs, self‐assembly of preassembled nanoassemblies, and macroscopic self‐assembly are systematically summarized. Finally, a personal perspective on self‐assembly and the developing outlook is also involved.